Effects of ambient ozone exposure on circulating extracellular vehicle microRNA levels in coronary artery disease patients. Issue 9 (2nd May 2020) - Chen, Hao; Xu, Yunan; Rappold, Ana; Diaz-Sanchez, David; Tong, Haiyan
ABSTRACT: Exposure to ambient air pollutants such as ozone (O3 ) and particulate matter (PM) is associated with increased cardiovascular morbidity and rate of mortality, but the underlying biological mechanisms have yet to be described. Emerging evidence shows that extracellular vehicle (EV) microRNAs (miRNAs) may facilitate cell-to-cell and organ-to-organ communications and play a role in the air pollution-induced cardiovascular effects. This study aims to explore the association between air pollutant exposure and miRNA changes related to cardiovascular diseases. Using a panel study design, 14 participants with coronary artery diseases were enrolled in this study. Each participant had up to 10 clinical visits and their plasma samples were collected and measured for expression of miRNA-21 ( miR-21), miR-126, miR-146, miR-150, and miR-155 . Mixed effects models adjusted for temperature, humidity, and season were used to examine the association between miRNA levels and exposure to 8-hr O3 or 24-hr PM2.5 up to 4 days prior. Results demonstrated that miR-150 expression was positively associated with O3 exposure at 1–4 days lag and 5day moving average while miR-155 expression tracked with O3 exposure at lag 0. No significant association was found between miRNA expression and ambient PM2.5 at any time point. β-blocker and diabetic medication usage significantly modified the correlation between O3 exposure and miR-150 expression where the link was more prominent among non-users. In conclusion, evidence indicated an association between exposure to ambient O3 and circulating levels of EV miR-150 and miR-155 was observed. These findings pointed to a future research direction involving miRNA-mediated mechanisms of O3 -induced cardiovascular effects.